Raba slovenščine in angleščine v fizičnem in virtualnem prostoru - Šabec, Nada (Slavistična revija, 2014)
The article discusses various ways in which Slovene and English function within the physical and virtual spaces of today's world. On the one hand English has undergone a process of differentiation into numerous mother tongue varieties, on the other we are witnessing tendencies toward its renewed homogenization in the role of a universal means of international communication. Special emphasis is placed on the influence of Global English on Slovene as well as on possible developmental trends.
Keywords: angleščina; English; English language; globalizacija; globalization; jezikovne spremembe; language changes; prostor; Slovene; Slovene language; slovenščina; space